Fluorescence of CdSe/ZnS quantum dots in toluene: effect of cyclic temperature. (February 2019) - Chen, Ying; Luan, Weiling; Zhang, Shaofu; Yang, Fuqian
Abstract: Quantum dots (QDs) are the potential material for the application in optical thermometry, and have been successfully applied to solar cells, LEDs, bio-labeling, structural health monitoring, etc. In this paper, we study the fluorescence properties of CdSe/ZnS QDs in toluene under the action of heating-cooling cycles. The experimental results show that, in a heating-cooling cycle, increasing temperature causes red-shift of the emission peak and the decrease of the PL intensity, and decreasing temperature causes blue-shift of the emission peak and the increase of the PL intensity. The surface structures of the QDs likely are dependent on the cycle numbers, which cause the change of the excited energy state of the QDs in toluene. The results presented in this paper reveals the strong effects of cyclic temperature on the photoluminescence characteristics of QDs.